2022
DOI: 10.1177/13634615221080231
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational trauma in Rwandan genocidal rape survivors and their children: A culturally enhanced bioecological approach

Abstract: Multiple theories, including attachment, family systems, and epigenetics, among many others, have been invoked to explain the mechanisms through which trauma is transmitted from one generation to the next. To move toward integration of extant theories and, thus, acknowledgement of multiple pathways for transmission of trauma, the authors explore the potential of applying a culturally enhanced bioecological theory to transgenerational trauma (TGT). Data from in-depth qualitative interviews in Rwanda more than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A loss of trust and social cohesion with both physical and cultural fragmentation continuing years after a genocide were additional social consequences (Akhavan et al., 2020; Vale, 2020). Six studies noted genocidal rape survivors’ experiences with poverty and financial hardship (Crosby et al., 2016; Denov & Piolanti, 2019; Kahn & Denov, 2022; Kantengwa, 2014; Russell et al., 2016; Walstrom et al., 2013). Noted poverty‐related issues included poor access to medical care and associated resources and the loss of housing.…”
Section: Resultsmentioning
confidence: 99%
“…A loss of trust and social cohesion with both physical and cultural fragmentation continuing years after a genocide were additional social consequences (Akhavan et al., 2020; Vale, 2020). Six studies noted genocidal rape survivors’ experiences with poverty and financial hardship (Crosby et al., 2016; Denov & Piolanti, 2019; Kahn & Denov, 2022; Kantengwa, 2014; Russell et al., 2016; Walstrom et al., 2013). Noted poverty‐related issues included poor access to medical care and associated resources and the loss of housing.…”
Section: Resultsmentioning
confidence: 99%
“…Erjavec and Volčič (2010), in their study of adolescents born as a result of rape conducted in Bosnia and Herzegovina, revealed key themes, including adolescents experiencing a continued sense of hostility and stigma even after the end of the war, and feeling as if they belong to the 'other'. Children were also found to experience guilt and reversed roles in the parental relationship, becoming carers of their mothers (Kahn and Denov, 2022). Rwandan cultural relational ontologies are constituted by social networks and defined by relational roles such as that of a parent or a child (Eramian, 2017).…”
Section: The Aftermath Of Genocidal Sexual Violencementioning
confidence: 99%
“…8 To deal with their challenging condition, some turned to substance abuse or sex work to act out their suffering. 3,4,8,9 Though these offspring are a vulnerable population with a greater risk of experiencing stigma, mental disorders, substance abuse, and poor academic performance, 1,[5][6][7] many studies have generally focused on lived and mothering experiences, 2,4,[9][10][11][12][13][14][15][16] and mothers' needs and intervention. 3,17 Few studies of children have emphasised children's challenges and psychosocial problems, 11,18-21, experience of disclosure, 22 and children's needs.…”
Section: Introductionmentioning
confidence: 99%
“…Though these offspring are a vulnerable population with a greater risk of experiencing stigma, mental disorders, substance abuse, and poor academic performance, 1 , 5–7 many studies have generally focused on lived and mothering experiences, 2 , 4 , 9–16 and mothers’ needs and intervention. 3 , 17 Few studies of children have emphasised children’s challenges and psychosocial problems, 11 , 18–21 , experience of disclosure, 22 and children’s needs. 23 A study by Hogwood et al, 22 primarily aimed at exploring how young people experienced the disclosure and how this affected their sense of identity revealed that the supported disclosure helped children to understand more fully themselves, their identity, and parentage, and to answer questions about their absent or unknown fathers and the way they had been treated in their families and the community.…”
Section: Introductionmentioning
confidence: 99%